Nonlinear Power Inductors for Large Current Crest Factors - Alexander Stadler; Tobias Stolzke; Christof Gulden (Journal of Engineering)
A practical method is presented: how to adjust the inductance curve of a nonlinear (saturable) inductor with respect to a desired shape. For this purpose, a nonlinear model was developed based on finite element method (FEM). It is shown how a highly efficient construction with low stray fields and maximum package density can be achieved. Different prototype inductors were realized to illustrate the practical capability of photovoltaic (PV) inverters as well as active power factor correction (PFC) applications. All simulations are verified by means of experimental data drawn from electrical measurements.